Calendar for Southern Highbush Blueberry Management in Florida - Doug Phillips; Jeffrey G. Williamson; Philip F Harmon; Oscar E. Liburd; Peter J. Dittmar (EDIS)
Southern highbush blueberries (SHB) are commercially grown throughout Florida in both deciduous and evergreen systems. This calendar addresses general management requirements on a monthly basis for conventional (nonorganic) systems and should be used in coordination with other UF/IFAS EDIS publications. This new 7-page article, published by the UF/IFAS Horticultural Sciences Department, was written by Douglas A. Phillips, Jeffrey G. Williamson, Philip F. Harmon, Oscar E. Liburd, and Peter J. Dittmar.